Role of Senate in Federalism: An Evidence from Pakistan in the Post 18th Amendment Scenario - Hira Riaz; Syed Mussawar Hussain Bukhari; Shahzad Ali Gill; Saba Javaid; Muhammad Hamid Murtza (Journal of Management Practices, Humanities and Social Sciences, 2021)
Federalism is a setup most suited to countries with diversity. A bicameral legislature has become the necessity of multicultural federations since it best satisfies the federating units’ needs by giving them equal representation to participate in the legislation and accountability processes. It also guarantees impartiality through providing a second deliberation on matters considered at the lower house overshadowed by the federating units with the majority population. In Pakistan, all constitutions had unicameral legislatures until the debacle of East Pakistan in 1971. After the unfortunate incident, it was felt that an upper house should check out the domination of the largest province in the central legislature with equal representation. So, the 1973 Constitution of the Islamic Republic of Pakistan came out with an upper house named Senate. Provincial autonomy was the long demanded right of provinces brought about by the 18th Amendment to the Constitution. The Amendment gave a new and dynamic role to the Senate. The present study intends to analyze the Senate’s role in the federation of Pakistan in the backdrop of the 18th Amendment. By utilizing primary and secondary data sources, this study takes an analytical approach to address the research question. For this purpose, the authors have conducted semi-structured interviews with the Senators (n=6) belonging to all four provinces of Pakistan to bring empirical evidence concerning the role of the Senate as the House of the Federation. The study underscores that the indirect election of the senators, insignificant legislative powers of the Senate, parliamentary nature of the political system, and the resultant bulldozing of legislative proposals by the presidential ordinances and joint sessions of the parliament severely curtail the powers of the Senate. The study concludes that the members of the Senate should be directly elected so that their dependency on the respective provincial assemblies is minimized. The legislative powers of the Senate should be enhanced along with veto power. In case of a joint session of the parliament, one vote of the Senate should be counted as equal to three votes of the NA. With a humble contribution to theoretical and practical fields, the study describes its limitations and presents directions for future research.